2019
DOI: 10.1002/pon.5129
|View full text |Cite
|
Sign up to set email alerts
|

The effects of weight loss and metformin on cognition among breast cancer survivors: Evidence from the Reach for Health study

Abstract: Objective Breast cancer survivors experience problems with cognition that interfere with daily life and can last for years. In the general population, obesity and diabetes are risk factors for cognitive decline, and weight loss can improve cognition; however, the impact of intentional weight loss on cancer survivors' cognition has not been tested. We investigated the impact of weight loss and metformin on changes in cognitive function in a sample of breast cancer survivors. Methods Overweight/obese postmenopau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…In four double-blind randomized controlled studies (DRCTs), the effect of metformin versus placebo on cognitive performance was evaluated in 325 patients with and without diabetes (DM). The dose of metformin used in these studies was 1500–2000 mg per day and the duration of treatment was 16–48 weeks (Luchsinger et al, 2016; Guo et al, 2014; Hartman et al, 2019; Imfeld et al, 2012). The quality of all trials was high.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In four double-blind randomized controlled studies (DRCTs), the effect of metformin versus placebo on cognitive performance was evaluated in 325 patients with and without diabetes (DM). The dose of metformin used in these studies was 1500–2000 mg per day and the duration of treatment was 16–48 weeks (Luchsinger et al, 2016; Guo et al, 2014; Hartman et al, 2019; Imfeld et al, 2012). The quality of all trials was high.…”
Section: Resultsmentioning
confidence: 99%
“…Out of four trials, three (Guo et al, 2014; Hartman et al, 2019; Luchsinger et al, 2016) were eligible for inclusion in the meta-analysis. The pooled effect was non-significant with SMD (standardized mean difference) equal to 0.50, 95% CI = [−0.2, 1.20], and I 2 = 89.3% in a random-effect analysis (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Hartman et al (2019) found that metformin might not positively affect neurocognitive functioning among BC survivors in general. However, verbal functioning could be enhanced by weight loss among individuals with higher BMI 85 .…”
Section: Discussionmentioning
confidence: 95%
“…The study concluded that use of metformin on obese cancer survivors did not provide any improvements in cognitive complaints, but did show a signi cant improvement in verbal functioning (p = 0.009). 34 Lawrence et al used donepezil as an intervention in 32 BCS with reported CICI compared to control group (n = 32). The intervention group performed slightly better on the Hopkins Verbal Learning Test-Revised (p = 0.033) and the HVLT-R Discrimination (p = 0.036) compared to the control group.…”
Section: Interventionsmentioning
confidence: 99%